HUMAN RIGHTS-BASED AGRARIAN CONFLICT RESOLUTION IN LAND ACQUISITION FOR NATIONAL STRATEGIC PROJECTS - Gloria Gita Putri Ginting; Ayu Kurnia Sari (PT. Radja Intercontinental Publishing, 2025)
However, its implementation often leads to agrarian conflicts related to unequal land ownership, unclear rights, differences in compensation, limited community participation, and threats to the sustainability of livelihoods for affected groups. These issues demonstrate that agrarian conflicts are not solely related to land administration but also touch upon human rights dimensions. This study aims to analyze the resolution of agrarian conflicts in land acquisition for National Strategic Projects from a human rights perspective and to formulate a more just, participatory, and sustainable approach to resolution. The study employed a descriptive qualitative method with a literature review and document study approach. Data were obtained from laws and regulations, policy documents, state agency reports, scientific articles, and literature related to agrarian conflicts and human rights. The results indicate that there is still a gap between procedural certainty and substantive justice in land acquisition. Project acceleration also has the potential to narrow the space for participation if it is not accompanied by transparency and protection of community rights. Therefore, conflict resolution needs to be carried out through dialogue, meaningful participation, prevention of criminalization, effective complaint mechanisms, and restoration of the lives of affected communities by placing respect for human rights as the main basis for development.